2019
DOI: 10.1021/acsaelm.9b00172
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Capacitance Characteristics of DNA Thin Layers Embedded with Semiconducting ZnO and CuO Nanoparticles

Abstract: Advances in semiconductor metal oxide nanoparticles (NPs), such as ZnO and CuO NPs, have allowed the construction of novel and efficient optoelectronic devices and sensors. Deoxyribonucleic acid (DNA) molecules, which are among the most versatile biomaterials, have proven to be a useful template for arranging and decorating nanomaterials, significantly enhancing their specific functionalities. In this study, we fabricated p-type ZnO and n-type CuO NP-embedded DNA thin layers via a facile drop-casting method. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The vibrational and stretching mode absorption band positions and their corresponding band assignments are shown in Table S1 in the Supporting Information. [ 42,44–46 ] The decreased peak intensities and peak shifts confirm physical manipulation of the strong interactions among the MoS 2 NPs, CQDs, and CDNA (compared to pristine CDNA). The MoS 2 NPs and CQDs tend to be wrapped by the CDNA molecules, resulting in electrostatic and noncovalent interactions among CDNA, the MoS 2 NPs, and CQDs.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The vibrational and stretching mode absorption band positions and their corresponding band assignments are shown in Table S1 in the Supporting Information. [ 42,44–46 ] The decreased peak intensities and peak shifts confirm physical manipulation of the strong interactions among the MoS 2 NPs, CQDs, and CDNA (compared to pristine CDNA). The MoS 2 NPs and CQDs tend to be wrapped by the CDNA molecules, resulting in electrostatic and noncovalent interactions among CDNA, the MoS 2 NPs, and CQDs.…”
Section: Resultsmentioning
confidence: 88%
“…Table S2 in the Supporting Information shows the appreciable changes in peak heights, full widths at half maxima, peak areas, atomic percentages, and binding energy changes of CDNA and MoS 2 -CQD-CDNA. [42,49,50] The MoS 2 -CQD-CDNA nanocomposite was then used to develop a highly efficient TENG device. In the single-electrode configuration, the nanocomposite could generate an electrical output due to triboelectric and electrostatic inductions through repetitive contact/noncontact cycles with the PDMS surface (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past few decades, utilizing biomolecules as support materials for different nanomaterials has attracted a huge amount of attention due to their unique behavior. Among the various biomolecules explored, the intriguing properties of deoxyribonucleic acid (DNA) such as its high dielectric constant, large band gap, and readily available negatively charged phosphate groups have made it a promising candidate for use as a template or scaffold to construct various nanostructures. , DNA has been frequently used as an efficient host material to incorporate several other materials, viz., nanoparticles, metal ions, drugs, and many more. Kundu et al used DNA as a template to construct one-dimensional nanostructures with different metal oxide nanoparticles including TiO 2 , MnO 2 , SnO 2 , and SrTiO 3 and explored its use in supercapacitor applications. However, studies have shown poor cycling stability due to the utilization of harsh chemicals and high temperatures during synthesis. These conditions can destroy the basic structure of DNA and hence cause poor stability.…”
Section: Introductionmentioning
confidence: 99%
“…These modifications of DNA mean it can be effectively used in various organic and inorganic applications [4,5]. In addition, DNA has been exploited as an efficient scaffold material for hosting functional nanomaterials such as ions, nanoparticles, drugs, dyes, and carbonbased materials through intercalation, electrostatic interaction, groove binding as well as slight modifications with small molecules in order to obtain specific functionalities [6][7][8][9][10][11][12][13]. Consequently, development of nanomaterial-embedded DNA complexes using simple procedures and their characterization with specific apparatus are of interest and essential for exploring the various potential applications in both science and engineering.…”
Section: Introductionmentioning
confidence: 99%